Morphological and mechanic analysis of the union of the adhesive system with healthy dentine and after caries removal - Okida, Ricardo Coelho [UNESP]; Da Silveira Okida, Daniela Secches [UNESP]; Homse, Vitor [UNESP]; Machado, Lucas Silveira [UNESP] (My University, 2017)
Aim: This “in vitro” study was to evaluate the formation of the hybrid layer of adhesion and resinous tags of a resinous adhesive system in a healthy dentinal substratum and in one after the removal of the carious tissue, including its behavior against a shear mechanical test. Materials & Methods: Fifty human teeth indicated for extraction were used, and divided in 2 groups: 25 teeth were healthy and the other 25 presented caries at the dentin level. The removal of the carious tissue was made with the use of manual and rotator instruments. After the adhesive procedures, as recommended by the manufacturers, 10 specimens from each group were decalcified in a solution of formic acid/sodium citrate, cut in a thickness of 6 micrometers and stained with the Brown & Brenn method, to posteriorly analyze and measure the hybrid layer of adhesion and the resinous tags with a common optic microscope (AXIOPHOT) (400X). The other 15 specimens from each of the two groups were submitted to shear union testing with the considered dental substrates. Results: It was observed that after the removal of the carious dentine, the depth of the hybrid layer, as well as the resinous tags, was significantly lower compared to the ones with healthy dentine. Much like the shear test, the adhesive system performed a better union resistance in healthy dentine, whereas, the removal of dentine carious tissue was observed with post caries. Conclusion: It was concluded that the carious process reduces the effectiveness of the resinous adhesive system performance.
Keywords: Dental caries; Dentin-bonding agents; Shear strength